2014
DOI: 10.1093/infdis/jiu232
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Pediatric Infectious Diseases

Abstract: The success of the immune response is finely balanced between, on the one hand, the need to engage vigorously with, and clear, certain pathogens; and, on the other, the requirement to minimize immunopathology and autoimmunity. Distinct immune strategies to achieve this balance have evolved in females and males and also in infancy through to adulthood. Sex differences in outcome from a range of infectious diseases can be identified from as early as fetal life, such as in congenital cytomegalovirus infection. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
255
3
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(306 citation statements)
references
References 58 publications
32
255
3
16
Order By: Relevance
“…After this age, the rate of illness falls as the first infections induce a certain level of immunity, which protects against following incidences (Yu et al, 2015). Gender is also important, because of differences in immune system functioning between girls and boys, and because girls have been shown to have lower morbidity and mortality rates than boys (Muenchhoff & Goulder, 2014).…”
Section: Control Factorsmentioning
confidence: 99%
“…After this age, the rate of illness falls as the first infections induce a certain level of immunity, which protects against following incidences (Yu et al, 2015). Gender is also important, because of differences in immune system functioning between girls and boys, and because girls have been shown to have lower morbidity and mortality rates than boys (Muenchhoff & Goulder, 2014).…”
Section: Control Factorsmentioning
confidence: 99%
“…These sex differences are thought to be due to biological and behavioral differences between men and women, but the precise mechanisms are poorly understood. Furthermore, the effects of sex on infectious disease susceptibility seem to vary with age [2,3]. For example, previous reports suggest that male subjects tend to have an increased susceptibility to infectious diseases during childhood, whereas female subjects are at greater risk of infection during pregnancy [2].…”
mentioning
confidence: 99%
“…Previous studies have shown that girls produce stronger immune responses to several viruses [12,13]. Thus, our observation may reflect a difference in immune responsiveness to influenza A virus rather than in the number of infections per se.…”
Section: Discussionmentioning
confidence: 53%